ANALISIS KEMAMPUAN BERPIKIR LOGIS MATEMATIS SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Ruhama, Mustafa A H; Yasin, Nurya; La Nani, Karman (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2020)
This study aims to describe the mathematical logical thinking ability of students of SMP Negeri 1 Ternate on systems of linear equations in two variables materials. This research uses a qualitative research. Subject of this study were three students of class VIII-J SMP Negeri 1 Ternate. The data collection stage was conducting tests, categorizing students according to the KBLM level based on the test results, and conducting interviews with research subjects. The data analysis used in this study was to analyze the data from the test results and interviews. The results showed that students at KBLM Level 2 were able to say and write down what was known and what was asked about the questions correctly, were able to use the steps to solve systems of linear equations in two variables and these steps were correct, were able to provide arguments about all steps-steps to solve systems of linear equations in two variables, and be able to draw conclusions correctly on the final answer. Students at KBLM Level 2 were able to say and write down what was known and not write down what is asked, able to use the steps to solve systems of linear equations in two variables and these steps are correct, able to provide arguments about all steps to solve systems of linear equations in two variables, and able to draw conclusions correctly on the final answer. Students at KBLM Level 2 were able to say and write down what was known and not write down what is asked, can use the steps to solve systems of linear equations in two variables but make calculation errors in these steps, do not provide arguments about all the steps solve systems of linear equations in two variables, and do not draw conclusions correctly on the final answer